Using the family APGAR score to evaluate family relationships in the elderly: an integrative review - Ivania Vera; Roselma Lucchese; Denize Bouttelet Munari; Adélia Yaeko Kyosen Nakatani (Universidade Federal de Goias, 2014)
The objective of this Integrative Literature Review was to systematize the knowledge on how the Family APGAR score has been used to identify the functionality of family relationships in the elderly. Method: a was performed of LILACS, MedLine, Pubmed and SciELO databases using the descriptors: "aged", "aged, 80 and over", "family relations" and "family", as they represent the triad elderly-family-family relationships, published in Portuguese, English and Spanish between the year 2000 and 2013. Results: thirteen articles met the inclusion criteria, all of which were evidence of non-experimental studies, descriptive or using a qualitative approach. The analyzed articles described the Family APGAR as an instrument used by a multidisciplinary team to measure family functionality based on the index person. The instrument is of quick application, easy to manage and interpret. Furthermore, it permits identifying family dysfunction of the elderly and caregivers, a condition that contributes to broadening the concept of relationships in the family setting. Descriptors: Aged; Family; Family Relations; Nursing.